Creating English Environment at School Through English Club Extracurricular - Afifah Maulina Astari; Muhamad Sofian Hadi (Jurnal Studi Guru dan Pembelajaran, 2022)
English proficiency has become something that should be mastered in this modern era. The limitations of educational institutions make the students lack mastery of the English language itself. Some schools solve the problem by making English extracurricular a “container” for students to express their interest and potential in English. This study aims to find out how the existence of an extracurricular English club can create a comfortable English environment for students. This study uses qualitative research with descriptive methods conducted through interviews and observations over 10 students as the respondence. The techniques for analyzing the data in this study used the Miles and Huberman model, including data reduction, data display, and drawing the conclusions. The results of the study found that the English club was a good means for students to practice English, as well as preparing students to be more mature and ready to compete